O-001 A Multicenter, Double-Blind, Placebo-Controlled Phase3 Study of Ustekinumab, a Human IL-12/23P40 mAB, in Moderate-Service Crohn's Disease Refractory to Anti-TFNα: UNITI-1. (March 2016) - Sandborn, William; Gasink, Christopher; Blank, Marion; Lang, Yinghua; Johanns, Jewel; Gao, Long-Long; Sands, Bruce; Hanauer, Stephen; Feagan, Brian; Targan, Stephan; Ghosh, Subrata; de Villiers, Wim; et al.
Abstract : Background: Interleukins 12&23 are implicated in the pathophysiology of Crohn's disease (CD). These pro-inflammatory cytokines are blocked by ustekinumab (UST). In a previous Phase 2b study (CERTIFI), 1 UST IV induction followed by SC maintenance was shown effective in moderate-severe CD refractory to anti-TNF therapy. This Phase 3 study examined the efficacy and safety of IV UST induction in these patients. Methods: Patients with moderate-severely active CD (CDAI 220–450) who previously failed or were intolerant to at least 1 TNF-antagonist were randomized (1:1:1) at Week (Wk) 0 to a single dose of IV placebo (PBO), UST 130 mg, or weight-based tiered UST dosing approximating 6 mg/kg (260mg [weight ⩽55 kg], 390mg [weight >55 kg and ⩽85 kg], 520mg [weight >85 kg]). The primary endpoint was clinical response at Wk6, defined as reduction from baseline in the CDAI score of >100 points; patients with baseline CDAI score >220 to <248 points were considered in clinical response if a CDAI score of <150 was present. At Wk8, patients either transitioned to the IM-UNITI maintenance study or were followed to Wk20. Results: The 741 randomized patients had a history of TNF-antagonist failure, with baseline median CDAI of 317, CRP of 9.9 mg/L, and prior disease duration of 10.1 years. Of these, 51% had previously failed ≥2 anti-TNFs with 29.1%, 69.4%, and 36.4% of patients, respectively, satisfying protocol criteria for primary non-response, secondary non-response, or intolerance to at least one TNF antagonist. Statistical significance was demonstrated for the primary and all 4 major secondary endpoints at both IV doses. Clinical response at Wk6 (primary endpoint) was observed in 33.7% of the ∼6 mg/kg and 34.3% of the 130 mg UST groups versus 21.5% in PBO ( P = 0.003 and 0.002, respectively). Clinical remission (CDAI <150) at Wk8 was observed in 20.9% of the ∼6 mg/kg group and 15.9% of the 130 mg UST group versus 7.3% on PBO ( P < 0.001, P = 0.003, respectively). Clinical response at Wk8 was seen in 37.8% of the ∼6 mg/kg and 33.5% of the 130 mg UST groups, versus 20.2% on PBO (each P ⩽ 0.001). Proportion of patients with 70pt CDAI response at Wk6 was 43.8% of the ∼6 mg/kg and 46.1% of the 130 mg UST groups versus 30.4% in PBO ( P = 0.002 and <0.001, respectively) and at the first post-baseline Wk3 visit, 40.6% in ∼6 mg/kg and 38.4% in the 130 mg UST groups versus 27.1% in PBO ( P = 0.001 and P = 0.009, respectively), the final major secondary endpoint. Both IV UST induction doses additionally resulted in significant improvements in CDAI, IBDQ, CRP, fecal lactoferrin and calprotectin versus IV PBO. Proportions of patients with AEs, SAEs, and infections were similar in the UST and PBO groups. One opportunistic infection (listeria meningitis) was reported in the ∼6 mg/kg UST group. No malignancies, deaths, major adverse cardiovascular events, or TB occurred in UST-treated patients through Wk20. Conclusions: In a population of moderate-severe CD patients refractory to one or more prior TNF-antagonists, IV UST induced clinical response and remission and was well-tolerated throughout induction, confirming the previous positive induction data from the Phase 2b CERTIFI study.